 # Laplace transform of $$\displaystyle{f{{\left({t}\right)}}}={t}{e}^{{-{t}}}{\sin{{\left({2}{t}\right)}}}$$ Zane Decker 2022-04-14 Answered
Laplace transform of $f\left(t\right)=t{e}^{-t}\mathrm{sin}\left(2t\right)$
You can still ask an expert for help

## Want to know more about Laplace transform?

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it maggionmoo
Here is an approach.
$\mathcal{L}\left(\mathrm{sin}2t\right)=\frac{2}{{s}^{2}+{2}^{2}}=\frac{2}{{s}^{2}+4}$ , using the table.
$\mathcal{L}\left({e}^{-t}\mathrm{sin}2t\right)=\frac{2}{{\left(s+1\right)}^{2}+4}$ , using frequency shifting.
$\mathcal{L}\left(t{e}^{-t}\mathrm{sin}2t\right)=-\frac{d}{ds}\left(\frac{2}{{\left(s+1\right)}^{2}+4}\right)=\frac{4\left(s+1\right)}{{\left({\left(s+1\right)}^{2}+4\right)}^{2}}$ , using frequency differentiation.
###### Not exactly what you’re looking for? veselrompoikm
Let $f\left(t\right)=t{e}^{-t}\mathrm{sin}\left(2t\right)=tg\left(t\right)$ and $g\left(t\right)={e}^{-t}\mathrm{sin}\left(2t\right)={e}^{-t}h\left(t\right)$ with $h\left(t\right)=\mathrm{sin}\left(2t\right)$. So $F\left(s\right)=-{G}^{\prime }\left(s\right)$ and $G\left(s\right)=H\left(s+1\right)$ with $H\left(s\right)=\frac{2}{{s}^{2}+4}$